(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2017)
Gestational Trophoblastic diseases consist of a broadspectrum of conditions ranging from an uncomplicated partial hydatidiform molar pregnancy to stage -IV choriocarcinoma with cerebral metastasis. Incidence of hydatidiform mole with a co-existing live fetus varies between 0.005 to 0.01 % of all pregnancies. We report a case of partial molar pregnancy with alive term IUGR (intrauterine growth retardation) foetus. Diagnosis was made by sonographic findings of molar changes at her 28 weeks of gestation. Anomaly scan showed no fetal abnormality. At 40 weeks of pregnancy patient went to spontaneous labour and delivered a severely IUGR baby weighing 1.5 kg and it was morphologically normal. There was a single placenta; one third of it was replaced by molar tissue. As the singletone alive pregnancy with partial molar changes is extremely rare occurrence we reported the case here. J Bangladesh Coll Phys Surg 2016; 34(3): 164-167